Serum liver enzymes are associated with all‐cause mortality in an elderly population. (13th November 2013) - Koehler, Edith M.; Sanna, Donatella; Hansen, Bettina E.; van, Frank J.; Heeringa, Jan; Hofman, Albert; Tiemeier, Henning; Stricker, Bruno H.; Schouten, Jeoffrey N. L.; Janssen, Harry L. A.
Abstract Background & Aims Little is known about the association of serum liver enzymes with long‐term outcome in the elderly. We sought to clarify the association of serum gamma‐glutamyltransferase (GGT), alkaline phosphatase (ALP), alanine aminotransferase (ALT) and aspartate aminotransferase (AST) with all‐cause and cause‐specific mortality in an elderly population. Methods This study was embedded in the Rotterdam Study, a large population‐based cohort of persons aged 55 years or older. Cox‐regression analyses were performed to examine the association of baseline serum GGT, ALP, and aminotransferase levels with mortality, adjusted for age, sex, education, smoking status, alcohol intake, hypertension, diabetes mellitus, body mass index and total cholesterol levels. Liver enzyme levels were categorized according to sample percentiles; levels <25th percentile were taken as a reference. Results During a follow‐up of up to 19.5 years, 2997 of 5186(57.8%) participants died: 672 participants died of causes related to cardiovascular diseases (CVD) and 703 participants died of cancer. All serum liver enzymes were associated with all‐cause mortality (all P < 0.001). Moreover, GGT was associated with increased CVD mortality (P < 0.001), and ALP and AST with increased cancer‐related mortality (P = 0.03 and P = 0.005 respectively). Participants with GGT and ALP in the top 5% had the highest risk for all‐cause mortality (HR1.55; 95%CI 1.30–1.85 and HR1.49; 95%CI 1.25–1.78 respectively). AST and ALT <25th percentile were also associated with a higher risk of all‐cause mortality. Conclusions All serum liver enzymes were positively associated with long‐term mortality in this elderly population. Why participants with low ALT and AST levels have higher risk of mortality remains to be elucidated.